The secret garden - Burnett, Frances Hodgson, 1849-1924.; Lawrie, Robin (New York : Puffin Books, 1994)
A ten-year-old orphan comes to live in a lonely house on the Yorkshire moors where she discovers an invalid cousin and the mysteries of a locked garden.
"Complete and unabridged"--Cover p. [4].
6.5
5-8
Keywords: Gardens -- Fiction; Orphans -- Fiction; People with disabilities -- Fiction; Gardens -- Fiction; Orphans -- Fiction; Physically handicapped -- Fiction; Yorkshire (England) -- Fiction; Yorkshire (England) -- Fiction